1991
DOI: 10.1111/j.1755-3768.1991.tb02007.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital retinal arteriovenous communication associated with a full‐thickness macular hole

Abstract: We present here a patient suffering from an unilateral retinal arteriovenous communication, belonging to group 2 in Archer classification, associated to a homolateral vascular malformation into the ophthalmic artery area, and a full-thickness macular hole. This is the first case with such an association reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Although most macular holes are idiopathic, they are occasionally associated with trauma, high myopia, and retinal vascular diseases such as proliferative diabetic retinopathy [1], hypertensive retinopathy [2], and congenital retinal arteriovenous communication [3]. A few studies have reported that rupture of a retinal arterial macroaneurysm might result in macular hole formation [4][5][6][7].…”
Section: Introductionmentioning
confidence: 98%
“…Although most macular holes are idiopathic, they are occasionally associated with trauma, high myopia, and retinal vascular diseases such as proliferative diabetic retinopathy [1], hypertensive retinopathy [2], and congenital retinal arteriovenous communication [3]. A few studies have reported that rupture of a retinal arterial macroaneurysm might result in macular hole formation [4][5][6][7].…”
Section: Introductionmentioning
confidence: 98%
“…MHs are also rarely associated with retinal vascular disease, such as proliferative diabetic retinopathy,5 hypertensive retinopathy6 and congenital retinal arteriovenous communication 7 8. With respect to retinal arterial macroaneurysm, only a few cases of MH associated with the rupture of a macroaneurysm have been reported 8 9 10 11 12 13.…”
mentioning
confidence: 99%